JINR: the initiator of future discoveries. (March 2016) - Matveev, V A
Abstract: On 26 March 2016, the Joint Institute for Nuclear Research (JINR) will mark its 60th anniversary as an internationally known research center that is a unique example of how fundamental theoretical and experimental studies can be integrated with the development and application of cutting-edge technologies and with university education. JINR member states number 18, of which Hungary, Germany, Egypt, Italy, Serbia, and the Republic of South Africa are each under a government-level cooperation agreement with the institute. Three factors combine to form a solid foundation on which JINR bases its work: commitment to traditions of internationally renowned research schools; unique performance hardware capable of solving problems of current interest in various fields of modern physics; and status as a UN intergovernmental body. Ranked high within the world's scientific community, the institute has conducted a wide range of research and trained high quality research personnel for its member states over the period since its foundation. In accordance with its Charter, JINR is open to participation by all interested states and ensures equal and mutually beneficial cooperation among them.